Supersonic impinging jet noise reduction using a hybrid control technique. (21st July 2015) - Wiley, Alex; Kumar, Rajan
Abstract: Control of the highly resonant flowfield associated with supersonic impinging jet has been experimentally investigated. Measurements were made in the supersonic impinging jet facility at the Florida State University for a Mach 1.5 ideally expanded jet. Measurements included unsteady pressures on a surface plate near the nozzle exit, acoustics in the nearfield and beneath the impingement plane, and velocity field using particle image velocimetry. Both passive control using porous surface and active control with high momentum microjet injection are effective in reducing nearfield noise and flow unsteadiness over a range of geometrical parameters; however, the type of noise reduction achieved by the two techniques is different. The passive control reduces broadband noise whereas microjet injection attenuates high amplitude impinging tones. The hybrid control, a combination of two control methods, reduces both broadband and high amplitude impinging tones and surprisingly its effectiveness is more that the additive effect of the two control techniques. The flow field measurements show that with hybrid control the impinging jet is stabilized and the turbulence quantities such as streamwise turbulence intensity, transverse turbulence intensity and turbulent shear stress are significantly reduced.